LDA Application Methods Laser Doppler Anemometry for Fluid Dynamics - Zhang, Zhengji (Experimental Fluid Mechanics, 2010)
This technical book considers the application aspect of LDA techniques. Starting from the basic theories that are crucial for LDA users, the main subject of the book is focused on diverse application methods. It deals in reality with universal methodical techniques which are directly related to the practical flow measurements and have been mostly developed in the last 15 years. The book thus gives to the first time an application reference for LDA users in improving the optical conditions and enhancing the measurement accuracies. It also provides the guidelines for simplifying the measurements and correcting measurement errors as well as for extending the application areas of LDA techniques. Besides the treatments of some traditional optical and flow mechanical features influencing the measurement accuracies, the book shows a broad spectrum of LDA application methods in the manner of measuring the flow turbulence, resolving the secondary flow structures, quantifying the optical aberrations at measurements of internal flows etc.. Thus it also supports the further developments of both the hard- and software of LDA instrumentations.